Changing the Image of Islam and Muslim World: Indonesian Exercise - Taher, Tarmizi (Studia Islamika, 1996)
This paper was originally a public lecture text of former Minister of Religious Affairs. H. Tarmizi Taher, MD, at the Center for the Study of World Religions, Harvard University, USA., On 8 November 1995, discussed the Indonesian Muslim religious discourse in relation to inter-religious relations.DOI: 10.15408/sdi.v3i2.805